Criteria for selecting third-party logistics service providers: Systematic Literature Review - Setyawan, Iwan; Rizkyah, Alika Eka (Operations Excellence: Journal of Applied Industrial Engineering, 2024)
Third-party logistics (3PL) is a strategic business partner for companies in carrying out company business activities that are outsourced or cannot be handled themselves. Mistakes in choosing a 3PL can have negative impacts on the company such as financial losses, reducing service quality, reducing customer trust, reducing the company's image, and so on. This article aims to classify third-party logistics based on current issue trends, the methods used in selecting criteria, and what criteria they produce. Using Systematic Literature Review, researchers reviewed, classified, and analyzed 56 relevant articles published in the 2020-2023 period from the Scopus database. The results of this review reveal that 3PL providers can be classified based on issue trends and company goals in selecting them, namely Traditional 3PL, Sustainable 3PL, Sustainable-resilient 3PL, Green 3PL, Gresilient 3PL, Traditional Third-Party Reverse Logistics, and Sustainable Third-Party Reverse Logistics. The priority criteria in selecting a 3PL provider are closely related to the 3PL classification, the industrial sector and business activity being outsourced, the country where the company operates, and the dimensions or attributes used in developing the criteria.